Ob-gyn Wellness Overall and by Gender in a Large Integrated Health Care System During the Pandemic [A73]. (May 2022) - Gregg, Laurie C.; Cobb, Jill Kacher; Stults, Cheryl D.; Dillon, Ellis; Deng, Sien
Abstract : INTRODUCTION: Pre-pandemic research indicated that 35-45% of physicians had symptoms of burnout. We examined the wellness of obstetrician-gynecologist (ob-gyn) clinicians twice during the pandemic. METHODS: Surveys were distributed in the summer and fall of 2020 to clinicians at eight medical groups and 17 hospitals affiliated with Sutter Health across Northern California. Bivariate analyses (e.g., chi-square test for categorical variables) and multivariate logistic regression models were used to test for statistical significance. RESULTS: A total of 7, 732 surveys were completed with 488 respondents from obstetrics and gynecology (393 women, 86 men, 5 missing gender). Burnout was more common among women than men (summer: 37.9% vs. 10%, P =.007; fall: 35.7% vs. 17.3%, P =.017). Fewer women than men believed their concerns would be acted upon (summer: 43.7% vs. 69.7%, P =.011: fall: 57.3% vs. 76.5%, P =.018). More women than men indicated that caregiving responsibilities impacted work (summer: 33.1% vs. 6.2%, P =.004; fall: 36.1% vs. 8.3%, P =.013). Compared to all specialties, a higher proportion of ob-gyn clinicians reported needing mental health support (summer: 19.4% vs. average 13.3%; fall 22.6% vs. average 14.6%). After adjusting for sex and age, ob-gyns still showed a higher odds of desire for mental health support than most other specialties. CONCLUSION: Women in obstetrics and gynecology experience more negative impacts with regards to wellness, feeling heard, and caregiving responsibilities when compared to their male colleagues. Compared to other specialties, more ob-gyn clinicians desired mental health support. Wellness efforts in our specialty should focus on addressing concerns, caregiving responsibilities, and mental health access.